Influence of Pictorial Crossword Puzzle Media Toward Vocabulary Mastery and Initial Writing Skills of Elementary School Students - Maududi, Ahmad; Purwanto, Edy; Awalya, Awalya (Journal of Primary Education, 2018)
The research aims to analyze the influence of pictoral crossword puzzle media toward vocabulary mastery and initial writing skills of the 1st grade of elementary school in the academic year of 2017/2018. The subjects in this study were 38 student of 1st grade of SDN Sampangan 01 as an experiment class and 34 student of 1st grade of SDN Bendan Ngisor as an control class. The experimental design in this research was quasi-experimental design with nonequivalent control group design. The results of the research on vocabulary mastery in the experimental class obtained n-gain of 0.54 in moderate category, while in the control class obtained n-gain of 0.03 in low category. Furthermore, the results of the research on initial writing skills of the experimental class obtained n-gain of 0.35 in moderate category, while the control class obtained n-gain of 0.11 in low category. Thus, it can be concluded that the using of pictorial crossword puzzle media affect to vocabulary mastery and initial writing skills. From these results, it is suggest to teachers to use pictorial crossword puzzles media in learning process in order to enhance vocabulary mastery and initial writing skills.